Engineering Faculty Perspectives on Bachelors’ Student Mathematical Prerequisites - Paudel, Krishna Chandra (Journal of Science and Technology, 2024)
This study explores engineering faculty perspectives concerning the adequacy and relevance of Nepal’s secondary level mathematics curriculum as a foundation for undergraduate engineering education. Through interpretative qualitative research involving purposively selected six engineering professors from two universities in Nepal, this study examines the alignment between secondary mathematics education and engineering program requirements through in-depth interviews. The major themes that emerged were contents sufficiency, sequential consistency, contextual pedagogical practice and unfamiliarity exam system. The results of the research can assist mathematics curriculum developers and teachers in secondary and undergraduate levels.